Transverse momentum distribution and nuclear modification factor of charged particles in p + Pb Collisions at √sNN=5.02 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Fasel, Markus; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; et al. (Physical review letters, 2013)
The transverse momentum (pT) distribution of primary charged particles is measured in minimum bias (non-single-diffractive) p+Pb collisions at √sNN=5.02 TeV with the ALICE detector at the LHC. The pT spectra measured near central rapidity in the range 0.5<pT<20 GeV/c exhibit a weak pseudorapidity dependence. The nuclear modification factor RpPb is consistent with unity for pT above 2 GeV/c. This measurement indicates that the strong suppression of hadron production at high pT observed in Pb+Pb collisions at the LHC is not due to an initial-state effect. The measurement is compared to theoretical calculations.
Im Titel steht "sNN" unter dem Wurzelsymbol
Im Titel ist "NN" in sNN tiefgestellt
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, M. Fasel, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, M. Spyropoulou-Stassinaki, J. Stachel, J.H. Stiller, S. Vallero, M. Vasileiou, Y. Wang, B. Windelband, A. Zimmermann und weitere 950
Gesehen am 30.04.2021